Desert Pavement Disturbance and Artifact Taphonomy: A Case Study from the Eastern Libyan Plateau, Egypt. Issue 2 (30th January 2013) - Adelsberger, Katherine A.; Smith, Jennifer R.; McPherron, Shannon P.; Dibble, Harold L.; Olszewski, Deborah I.; Schurmans, Utsav A.; Chiotti, Laurent
<x xml:space="preserve">Abstract</x> Accretionary desert pavements on the eastern Libyan Plateau of central Egypt support a rich Middle and Upper Paleolithic artifact assemblage exhibiting intensive blank production and minimal tool production. These assemblages appear to be in primary context with numerous examples of lithic refits showing on‐site lithic production. However, the smallest (length ≤2.5 cm) archaeological fragments are recovered at a much lower rate on this desert pavement surface than expected given comparable data from lithic assemblages in cave and shelter contexts in France. Excavation of archaeological contexts on the Libyan Plateau reveals the loss of small artifact fragments into the subsurface due to aeolian accumulation of silts, whereas geomorphic examination of desert pavement surfaces suggests a potential for relatively isolated bioturbation as a source of lateral and vertical disturbance of desert pavement surfaces over small areas. Archaeologists should be aware of the potential for long‐term assemblage stability as well as small artifact burial in surficial desert pavement contexts.